Dandelion extract inhibits triple-negative breast cancer cell proliferation by interfering with glycerophospholipids and unsaturated fatty acids metabolism - Wang, Shan; Hao, Hui-feng; Jiao, Yan-na; Fu, Jia-lei; Guo, Zheng-wang; Guo, Yang; Yuan, Yuan; Li, Ping-ping; Han, Shu-yan (Frontiers in Pharmacology, 2022)
Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype with limited treatment options and a poor prognosis. TNBC exists widely reprogrammed lipid metabolism, and its metabolic-associated proteins and oncometabolites are promising as potential therapeutic targets. Dandelion (Taraxacum mongolicum) is a classical herbal medicine used to treat breast diseases based on traditional Chinese medicine theory and was reported to have antitumor effects and lipid regulatory capacities. Our previous study showed that dandelion extract was effective against TNBC. However, whether dandelion extract could regulate the lipid metabolisms of TNBC and exert its antitumor effects via interfering with lipids metabolism remained unclear. In this study, an integrated approach combined with network pharmacology and multi-omics techniques (including proteomics, metabolomics, and lipidomics) was performed to investigate the potential regulatory mechanisms of dandelion extract against TNBC. We first determined the antitumor effects of dandelion extract in vitro and in vivo. Then, network pharmacology analysis speculated the antitumor effects involving various metabolic processes, and the multi-omics results of the cells, tumor tissues, and plasma revealed the changes in the metabolites and metabolic-associated proteins after dandelion extract treatment. The alteration of glycerophospholipids and unsaturated fatty acids were the most remarkable types of metabolites. Therefore, the metabolism of glycerophospholipids and unsaturated fatty acids, and their corresponding proteins CHKA and FADS2, were considered the primary regulatory pathways and biomarkers of dandelion extract against TNBC. Subsequently, experimental validation showed that dandelion extract decreased CHKA expression, leading to the inhibition of the PI3K/AKT pathway and its downstream targets, SREBP and FADS2. Finally, the molecular docking simulation suggested that picrasinoside F and luteolin in dandelion extract had the most highly binding scores with CHKA, indicating they may be the potential CHKA inhibitors to regulate glycerophospholipids metabolisms of TNBC. In conclusion, we confirmed the antitumor effects of dandelion extract against TNBC cells in vitro and demonstrated that dandelion extract could interfere with glycerophospholipids and unsaturated fatty acids metabolism via downregulating the CHKA expression and thus inhibiting PI3K/AKT/SREBP/FADS2 axis.